MODERASI PENDIDIKAN ISLAM AWAL ABAD 20 DI SUMATERA BARAT - Muhammad Qadafi; Iswantir M; Ali Akbar (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This journal discusses the beginning of the modernization of Islamic education in West Sumatra (Minangkabau). Library research methods. The results of the literature study show that the modernization of Islamic religious education in Minangkabau was initiated by the renewal of Islamic thought as a response to the social situation and conditions of the community and understanding of Islamic religious teachings at that time. The modernization process started from an educational institution called surau. From this surau the modernization movement grew and developed which later became a modern Islamic educational institution.